From epistemological truth to existential meaning in cognitive narrative psychotherapy - Gonçalves, Óscar F. (1994)
The notion of truth is discussed from the standpoint of narrative cognitive psychotherapy. The dominant clinical epistemological framework, based on the search for truth, needs to be replaced by an existential framework emphasizing the construction of alternative meanings. This article begins with a discussion of the paradigmatic shift from epistemological truth to existential meaning. The narrative is then presented as an ideal root metaphor for existence. Finally, the work of cognitive narrative psychotherapy is used to illustrate the construction and deconstruction of meaning in the clinical situation.